Dreptanie. Tadeusz Peiper i kino (po 1945 roku) - Wójtowicz, Aleksander ((Dy)fuzje: Związki literatury i sztuki w Polsce po 1945 roku, 2019)
The article deals with Tadeusz Peiper’s film writings (1947–1963). His constructivist theory was mainly concerned with the formal aspects of the cinema (color, sound). However, a very important role was played by nostalgy for harmony and community (Ferdinand Tönnies). It was articulated in the spirit similar to Martin Buber’s philosophy.